Microplastics in fresh and processed seafood – A survey of products sold in Germany - Julia Süssmann; Torsten Krause; Elke Kerstin Fischer; Elke Walz; Ralf Greiner; Sascha Rohn; Jan Fritsche (Food Control, 2026)

Pressure-assisted isolation of micro- and nanoplastics from food of animal origin with special emphasis on seafood - Julia Süssmann; Elke Walz; Birgit Hetzer; Ralf Greiner; Elke Kerstin Fischer; Sascha Rohn; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2025)
Recent studies have indicated the presence of micro- and nanoplastics in food of animal origin. To address the concerns regarding human dietary plastic uptake, extensive monitoring using validated analytical methods is required. However, a major challenge in analysis lies in the high complexity of preparing food samples rich in macromolecular content (e.g., proteins, complex lipids), such as seafood. Consequently, this study aimed to optimise sample preparation methods for seafood, meat, milk, honey, and eggs, ensuring negligible impact on plastic integrity. Sample matrices were digested using combinations of alkaline, oxidative, and enzymatic approaches, with incubation periods ranging from 6 to 16 h. Particles were rapidly isolated by pressure-assisted filtration, which retained particles in the lower micron range. This method, used for isolating microplastic from food, was compared to the commonly employed vacuum filtration technique. Pressure-assisted filtration improved filtration rates and matrix removal while demonstrating comparable impact on procedural contamination and polymer integrity to vacuum filtration. The feasibility of microplastic analysis was demonstrated using fluorescence imaging. In contrast to microplastics, nanoplastics (< 1 µm) have greater potential for negative biological effects due to their small size, warranting detailed analysis. However, their low particle mass, susceptibility for agglomeration, and the detection limits of conventional spectroscopic techniques pose unique analytical challenges. Addressing these challenges is essential for developing standardised methodologies, including certified food reference material, to enable safety assessments of micro- and nanoplastic in food. Graphical Abstract

Biomass & bioenergy IEA bioenergy: Update 72 - Paul Bennett; Jan Liebetrau; Uwe Fritsche (Biomass and Bioenergy, 2023)

Monitoring environmental radionuclide activity of the incident-relevant radionuclides 137Cs und 90Sr in animal feed and foodstuffs consumed in Germany - Gerhard Haase; Thomas Vagt; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2021)

Aflatoxin: food chain transfer from feed to milk - Hans-Georg Walte; Christine Schwake-Anduschus; Rolf Geisen; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2016)

Erratum zu: Integrierter Ansatz zur Beurteilung eines Aufsuchungsantrages auf Schiefergas in Hessen - Johann-Gerhard Fritsche; Jan Brodsky; Heiner Heggemann; Michaela Hoffmann; Martin Hottenrott; Matthias Kracht; Wolfgang Liedmann; Thomas Reischmann; Fred Rosenberg; Inga Schlösser-Kluger (Grundwasser, 2016)

Integrierter Ansatz zur Beurteilung eines Aufsuchungsantrages auf Schiefergas in Hessen - Johann-Gerhard Fritsche; Jan Brodsky; Heiner Heggemann; Michaela Hoffmann; Martin Hottenrott; Matthias Kracht; Thomas Reischmann; Fred Rosenberg; Inga Schlösser-Kluger (Grundwasser, 2016)

Lebensmittelkontrolle 2.0 - Alexandra Krewinkel; Sebastian Sünkler; Dirk Lewandowski; Niklas Finck; Boris Tolg; Lothar W. Kroh; Georg A. Schreiber; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2015)

Food Science Dialog 2015 - Jan Fritsche; Martin Holle; Katharina Riehn; Gregor Buschhausen-Denker; Till Sager; Antje Steinbicker (Journal of Consumer Protection and Food Safety, 2015)

Lebensmittelsicherheit & Verpackung - Gregor Buschhausen-Denker; Heiko Diehl; Astrid Droß; Jan Fritsche; Andreas Grabitz; Martin Holle; Andreas Luch; Karla Pfaff; Katharina Riehn; Oliver Robers; Eric Savary; Jochen Schlegel; et al. (Journal of Consumer Protection and Food Safety, 2015)

Lebensmittelsicherheit & Verpackung - Florian Baumann; Gregor Buschhausen-Denker; Andreas Butschke; Markus Fischer; Jan Fritsche; Martin Holle; Karen von Holleben; Ines Krause; Bernd van der Meulen; Katharina Riehn; Gereon Schulze Althoff; Cees Waalwijk (Journal of Consumer Protection and Food Safety, 2014)

Lebensmittelverbraucherinformation: Gesetzgebung, Instrumente und Auswirkung auf das Markt- und Ernährungsverhalten - Jan Fritsche; Martin Holle (Journal of Consumer Protection and Food Safety, 2013)

E-Commerce – Chancen und Risiken für die Lebensmittelbranche im 21. Jahrhundert - Jan Fritsche (Journal of Consumer Protection and Food Safety, 2012)

Aktuelle Trans-Fettsäuregehalte in Siedegebäcken - Jan Fritsche; Ryan Katzfey; Katharina D. Petersen; Gerhard Jahreis (Journal of Consumer Protection and Food Safety, 2012)

Online-Lebensmittelhandel und Strategien zur Kontrolle des virtuellen Lebensmittelmarktes - Alexandra Krewinkel; Boris Tolg; Jan Fritsche (Journal of Consumer Protection and Food Safety, 2011)

Identification and characterization of the cytoplasmic tungstate/molybdate-binding protein (Mop) from Eubacterium acidaminophilum - Kathrin Makdessi; Kathrin Fritsche; Andreas Pich; Jan R. Andreesen (Archives of Microbiology, 2004)

Cloning of Baeyer‐Villiger monooxygenases from Comamonas , Xanthobacter and Rhodococcus using polymerase chain reaction with highly degenerate primers - Jan B. Van Beilen; Frédéric Mourlane; Markus A. Seeger; Jasminka Kovac; Zhi Li; Theo H. M. Smits; Urban Fritsche; Bernard Witholt (Environmental Microbiology, 2003)
Summary To clone novel type 1 Baeyer‐Villiger monooxygenase (BVMO) genes, we isolated or collected 25 bacterial strains able to grow on alicyclic compounds. Twelve of the bacterial strains yielded polymerase chain reaction (PCR) fragments with highly degenerate primers based on the sequences of known and putative BVMOs. All these fragments were found to encode peptides homologous to published BVMO sequences. The complete BVMO genes and flanking DNA were cloned from a Comamonas , a Xanthobacter and a Rhodococcus strain using the PCR fragments as probes. BVMO genes cloned from the first two strains could be expressed to high levels in Escherichia coli using standard expression vectors, and the recombinants converted cyclopentanone and cyclohexanone to the corresponding lactones. The Rhodococcus BVMO, a putative steroid monooxygenase, could be expressed after modification of the N‐terminal sequence. However, recombinants expressing this protein did not show activity towards progesterone. An esterase homologue located directly upstream of the Xanthobacter BVMO gene and a dehydrogenase homologue encoded directly downstream of the Comamonas sp. NCIMB 9872 BVMO gene were also expressed in E. coli and shown to specify lactone hydrolase and cyclohexanol dehydrogenase activity respectively.